Th17 Cell Response in SOD1G93A Mice following Motor Nerve Injury - Allen Ni; Tao Yang; Nichole A. Mesnard-Hoaglin; Rafael Gutierrez; Evan B. Stubbs; Susan O. McGuire; Virginia M. Sanders; Kathryn J. Jones; Eileen M. Foecking; Junping Xin (Hindawi Limited, 2016)
An increased risk of ALS has been reported for veterans, varsity athletes, and professional football players. The mechanism underlying the increased risk in these populations has not been identified; however, it has been proposed that motor nerve injury may trigger immune responses which, in turn, can accelerate the progression of ALS. Accumulating evidence indicates that abnormal immune reactions and inflammation are involved in the pathogenesis of ALS, but the specific immune cells involved have not been clearly defined. To understand how nerve injury and immune responses may contribute to ALS development, we investigated responses of CD4+ T cell after facial motor nerve axotomy (FNA) at a presymptomatic stage in a transgenic mouse model of ALS (B6SJL SOD1G93A). SOD1G93A mice, compared with WT mice, displayed an increase in the basal activation state of CD4+ T cells and higher frequency of Th17 cells, which were further enhanced by FNA. In conclusion, SOD1G93A mice exhibit abnormal CD4+ T cell activation with increased levels of Th17 cells prior to the onset of neurological symptoms. Motor nerve injury exacerbates Th17 cell responses and may contribute to the development of ALS, especially in those who carry genetic susceptibility to this disease.